Developing an LMS-based of ESP course for Islamic undergraduate students - Dewi Hidayati; Utami Widiati; Evynurul Laily Zen; Francisca Maria Ivone (Social Sciences and Humanities Open)
Research on English for Specific Purposes (ESP) in the domain of Syariah Economics for Islamic undergraduate students reveals significant shortcomings in existing ESP models, which inadequately address the specialized linguistic and contextual needs of this field. The existing frameworks often lack tailored instructional strategies, highlighting a critical need for a targeted educational intervention. This study aims to address this gap by developing an LMS-based English course specifically designed for Syariah Economics. Utilizing a Research & Development approach grounded in the ADDIE Model (Analysis, Design, Development, Implementation, Evaluation), the research is implemented at STAI Diponegoro Tulungagung, Indonesia. The course's effectiveness is assessed in terms of its impact on language proficiency, student engagement, and academic performance. Results indicate that the course leads to significant improvements in students' ability to use specialized English terminology, enhances their engagement through interactive content, and positively affects their academic performance in Syariah Economics subjects. Recommendations for regular formative assessments should be integrated to ensure the course remains responsive to student needs and effectively addresses evolving challenges. Teaching strategies must be adapted to accommodate diverse learning styles, enhancing overall engagement and effectiveness. Additionally, evaluating the course's long-term effectiveness and scalability is crucial for determining its impact and sustainability. Innovative approaches, such as adaptive learning technologies and gamification, should be explored to further refine and enhance the course. Investigating the course's sustained impact and broader applicability across various educational contexts will be essential for advancing specialized language education and maximizing its benefits.